2011
DOI: 10.1212/wnl.0b013e31822dc7c8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chemokine levels, coronary heart disease, and ischemic stroke events

Abstract: Objectives:To quantify the association between systemic levels of the chemokine regulated on activation normal T-cell expressed and secreted (RANTES/CCL5), interferon-␥-inducible protein-10 (IP-10/CXCL10), monocyte chemoattractant protein-1 (MCP-1/CCL2), and eotaxin-1 (CCL11) with future coronary heart disease (CHD) and ischemic stroke events and to assess their usefulness for CHD and ischemic stroke risk prediction in the PRIME Study. Methods:After 10 years of follow-up of 9,771 men, 2 nested case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…Clinical information, computerized tomodensitometry scans (compatible signs), angiographic and autopsy data were used to distinguish between ischemic and hemorrhagic stroke events. 3,4 After 10 years of follow-up, the stroke event status was available for 95.1% of the cohort. Details of an assessment of the quality of data have been published elsewhere.…”
Section: Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical information, computerized tomodensitometry scans (compatible signs), angiographic and autopsy data were used to distinguish between ischemic and hemorrhagic stroke events. 3,4 After 10 years of follow-up, the stroke event status was available for 95.1% of the cohort. Details of an assessment of the quality of data have been published elsewhere.…”
Section: Follow-upmentioning
confidence: 99%
“…In the Prospective Epidemiological Study on Myocardial Infarction (PRIME), we have shown an incremental value of chemokines and adipocytokines in predicting ischemic stroke. 3,4 Biomarkers of hemostasis, inflammation, and endothelial activation represent further candidates for risk prediction, but evidence for their prospective association and prognostic relevance with regard to ischemic stroke is yet to be established. Moreover, simultaneous assessment of multiple biomarkers from distinct biological pathways, the so-called multimarker approach, has been hypothesized to enhance risk prediction in a clinically relevant manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, CXCL10 plays a pleiotropic role in prolonged leukocyte recruitment, astrocyte migration/activation, and neuron attachment/sprouting after focal stroke [14,15]. A previous study demonstrated the focal enhanced serum levels of CXCL10 in rat brains peaking at 1 h, a followed by a second peak at 3-6 h, and a third peak at 15 days after stroke [16]. In recent studies, CCL12, CCL5, and CXCL10 were associated with ischemic stroke independent of traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 81%
“…CXCL10 plays a pleiotropic role in prolonged leukocyte recruitment, astrocyte migration/activation, and neural attachment/sprouting following focal stroke [14,15]. In recent studies, CCL11, CCL5, and CXCL10 are associated with ischemic stroke independent of traditional cardiovascular risk factors [16].…”
Section: Introductionmentioning
confidence: 99%